Inovasi Pembangunan Desa Melalui Kepemimpinan Transformasional dan Catalytic Collaboration: Belajar dari Keberhasilan Pengelolaan Taman Ghanjaran di Desa Ketapanrame, Mojokerto - Endah Wahyuningsih; Shobirin Noer; Novy Yunas (Matra Pembaruan: Jurnal Inovasi Kebijakan, 2021)
Ghanjaran Park, which is located in Ketapanrame Trawas Village, Mojokerto, is part of the BUMDes business unit which has been successfully managed and has received many awards. This study aims to determine how the role of transformational leadership of village head in the governance of Ghanjaran Park is. This study used qualitative research methods. Data was collected by interviews, direct observation and documents related to the development of Ghanjaran Park. The data was obtained by using an in-depth interview instrument. There were 7 informants in this study, consisting of village heads, BUMDes staff, business actors, and village staff. Data analysis using inductive method. The results showed that the success of the BUMDEs in Ketapanrame Village, especially Ghanjaran Park, to get awards at the local, provincial and national levels could not be separated from the role of the village head. The village head of Ketapanrame has a central role, starting from planning (with the BPD creating village regulations related to village asset management), conducting an assessment of the potential of the village, to the success of empowering the community by increasing the participation of many parties. The village head’s character is also a role model for the wider community with its values, including honesty, openness, caring for others, responsibility and trust.